The Claussen Archaeological Site: Prehistory Of The Flint Hills - Rolfe Mandel (Symphony in the Flint Hills, 2011)
On a warm afternoon in May 2000, I was walking along Mill Creek in Wabaunsee County inspecting soils and sediment exposed in a steep stream bank that stands about thirty feet above the creek. It is a common routine for me. Most of my research involves reconstructing the geology, paleoecology, and archaeology of stream valleys, so I look for places where creeks and rivers have cut into their own deposits. These cutbanks are my “windows” into the past.
Keywords: Claussen; archaeology; archaeological; prehistory; Wabunsee County; paleoecology; geology; cutbanks; sediment; Mill Creek; Middle Ceramic period; hunter-gatheres; Kansas; floodplain; radiocarbon; dating; Paleoindian; Kansas Anthropological Association; anthropology; Dalton Period; dalton; KU Anthropology Department; prehistoric